Guide to clinical and diagnostic virology - Khare, Reeti (ASM Press, 2019)
"The explosion in clinical testing has been especially rapid in virology, where emerging viruses and growing numbers of viral infections are driving advances. This digestible view of the breadth and depth of information related to clinical virology provides a practical, working knowledge of the wide array of viruses that cause human disease. Introductory chapters cover the basics of clinical virology and laboratory diagnosis of infections, including virus structure, life cycle, transmission, taxonomy, specimen types and handling, and a comparison of assays used for detection"--Publisher's description.